2016
DOI: 10.1002/2015gl067326
|View full text |Cite
|
Sign up to set email alerts
|

Bias in streamflow projections due to climate‐induced shifts in catchment response

Abstract: Demand for quantitative assessments of likely climate change impact on runoff is increasing and conceptual rainfall‐runoff models are essential tools for this task. However, the capacity of these models to extrapolate under changing climatic conditions is questionable. A number of studies have found that model predictive skill decreases with changed climatic conditions, especially when predicting drier climates. We found that model skill only declines under certain circumstances, in particular, when a catchmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
93
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 45 publications
9
93
1
Order By: Relevance
“…Most recently, a prolonged drought occurred throughout southeastern Australia between ∼1997 and ∼2009 (noting that this period differs between studies due to different criteria for drought determination and different catchments being analyzed), which is the worst drought in the region since the instrumental era and is known as “the Millennium drought” (or “the Big dry”). The Millennium drought extended over all southeast Australia and resulted in very different hydrological behavior compared with shorter droughts in the same catchments [ Saft et al ., ]. Averaged over southeast Australian catchments, the Millennium drought was associated with ∼13% decrease in precipitation, amplified to be a ∼45% decline in streamflow with a ∼12% reduction in agricultural yield (i.e., measured per unit area) compared to predrought conditions [ Van Dijk et al ., ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most recently, a prolonged drought occurred throughout southeastern Australia between ∼1997 and ∼2009 (noting that this period differs between studies due to different criteria for drought determination and different catchments being analyzed), which is the worst drought in the region since the instrumental era and is known as “the Millennium drought” (or “the Big dry”). The Millennium drought extended over all southeast Australia and resulted in very different hydrological behavior compared with shorter droughts in the same catchments [ Saft et al ., ]. Averaged over southeast Australian catchments, the Millennium drought was associated with ∼13% decrease in precipitation, amplified to be a ∼45% decline in streamflow with a ∼12% reduction in agricultural yield (i.e., measured per unit area) compared to predrought conditions [ Van Dijk et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies on the Millennium drought mostly take the entire Southern Australia as a whole (or the entire Murray‐Darling Basin), resulting in a lack of detailed spatial information on the drought characteristics and its impacts at the catchment‐level (exceptions are Saft et al . []). Moreover, recovery from the Millennium drought, especially the hydrological components (i.e., streamflow and base flow), which directly indicate the recovery of available water resources, has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Water 2016, 8,171 Saft et al [67] also suggested processes linked to groundwater as a possible explanation behind the change in the hydrological functioning of catchments in the context of a prolonged dry period. The underground flow, coming from deep aquifer through the spring, gives a more delayed and smother response to climate than surface and shallow groundwater flow [66].…”
Section: Characterization Of Groundwater Level Dynamicmentioning
confidence: 99%